The creative reconstruction of the internet: Google and the privatization of cyberspace and DigiPlace - Zook, MA; Graham, M (Elsevier, 2007)
The Internet has often been portrayed as the ultimate leveler of information where existing hierarchies of power and privilege are undermined by meritocracy. Some websites and functions are, however, more equal than others. In particular, search engines such as Google have been a key means to construct meaning out of disorder. This ordering (or enclosing of the Internet commons), however, comes at a cost as a location within the top 10 Google search results, marks the boundary (albeit a fluid one) between the core and the periphery of the Internet. The recent incorporation of spatial elements into the Google indexing raises fresh and geographically relevant concerns. This article focuses on the construction, access and use of Google derived rankings to deploy geo-referenced information in the physical environment and the way this melding of code and place affects how people interact with place. Using the theoretical concept of DigiPlace this article analyzes how Google Maps and Google Earth are structured and shape what appears (and what does not) in cyberspace and DigiPlace. Of particular concern are the implications of a private corporation controlling this new space.